Biofabrication of a vascularized islet organ for type 1 diabetes. (April 2019) - Citro, Antonio; Moser, Philipp T.; Dugnani, Erica; Rajab, Taufiek K.; Ren, Xi; Evangelista-Leite, Daniele; Charest, Jonathan M.; Peloso, Andrea; Podesser, Bruno K.; Manenti, Fabio; Pellegrini, Silvia; Piemonti, Lorenzo; et al.
Abstract: Islet transplantation is superior to extrinsic insulin supplementation in the treating severe Type 1 diabetes. However, its efficiency and longevity are limited by substantial islet loss post-transplantation due to lack of engraftment and vascular supply. To overcome these limitations, we developed a novel approach to bio-fabricate functional, vascularized islet organs (VIOs) ex vivo . We endothelialized acellular lung matrixes to provide a biocompatible multicompartment scaffold with an intact hierarchical vascular tree as a backbone for islet engraftment. Over seven days of culture, islets anatomically and functionally integrated into the surrounding bio-engineered vasculature, generating a functional perfusable endocrine organ. When exposed to supra-physiologic arterial glucose levels in vivo and ex vivo, mature VIOs responded with a physiologic insulin release from the vein and provided more efficient reduction of hyperglycemia compared to intraportally transplanted fresh islets. In long-term transplants in diabetic mice, subcutaneously implanted VIOs achieved normoglycemia significantly faster and more efficiently compared to islets that were transplanted in deviceless fashion. We conclude that ex vivo bio-fabrication of VIOs enables islet engraftment and vascularization before transplantation, and thereby helps to overcome limited islet survival and function observed in conventional islet transplantation. Given recent progress in stem cells, this technology may enable assembly of functional personalized endocrine organs.